PRIO – a prospective integrative oncology registry: trial protocol - Werthmann, Paul G.; Lederer, Ann-Kathrin; Figura, Hannah Maja; Kramer, Klaus (Frontiers in Oncology, 2024)
BackgroundIntegrative Oncology (IO) – the use of lifestyle modifications, mind-body practices and natural products in oncology – is increasingly asked for by patients. The evidence base of IO is growing and IO measures are included in national guidelines. Still, many questions about IO remain unanswered or still show a poor evidence base.MethodData about demography, socioeconomic status, cancer disease and therapy, integrative oncology measures and patient reported outcomes will be collected in regular visits in oncological patients at the University Cancer Center Ulm, Germany. An expansion to further study centers is planned. After one year and at regular intervals, the registry will be evaluated and adapted accordingly.DiscussionThe PRIO registry builds a solid data base to evaluate the use of integrative oncology measures in cancer patients. It includes patient reported outcome measures to investigate quality of life and satisfaction with health services in this population. The registry aims to enhance transparency in IO use and wants to inform future research in IO. The trial has been registered in the German Clinical Trials Register (DRKS) under the ID DRKS00033250 and in the studyBox of the German Cancer Association under the ID ST-U173 on 18th December 2023. The trial was approved by the ethics committee of the University Medical Center Ulm under the number 375/23 on 7th December 2023.